Cardiometabolic risk factors and survival after cancer in the Women's Health Initiative. Issue 4 (5th November 2020) - Simon, Michael S.; Hastert, Theresa A.; Barac, Ana; Banack, Hailey R.; Caan, Bette J.; Chlebowski, Rowan T.; Foraker, Randi; Hovsepyan, Gayane; Liu, Simin; Luo, Juhua; Manson, JoAnn E.; Neuhouser, Marian L.; et al.
Abstract : Background: Cardiometabolic abnormalities are a leading cause of death among women, including women with cancer. Methods: This study examined the association between prediagnosis cardiovascular health and total and cause‐specific mortality among 12, 076 postmenopausal women who developed local‐ or regional‐stage invasive cancer in the Women's Health Initiative (WHI). Cardiovascular risk factors included waist circumference, hypertension, high cholesterol, and type 2 diabetes. Obesity‐related cancers included breast cancer, colorectal cancer, endometrial cancer, kidney cancer, pancreatic cancer, ovarian cancer, stomach cancer, liver cancer, and non‐Hodgkin lymphoma. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) adjusted for important predictors of survival. Results: After a median follow‐up of 10.0 years from the date of the cancer diagnosis, there were 3607 total deaths, with 1546 (43%) due to cancer. Most participants (62.9%) had 1 or 2 cardiometabolic risk factors, and 8.1% had 3 or 4. In adjusted models, women with 3 to 4 risk factors (vs none) had a higher risk of all‐cause mortality (HR, 1.99; 95% CI, 1.73‐2.30), death due to cardiovascular disease (CVD) (HR, 4.01; 95% CI, 2.88‐5.57), cancer‐specific mortality (HR, 1.37; 95% CI, 1.1‐1.72), and other‐cause mortality (HR, 2.14; 95% CI, 1.70‐2.69). A higher waist circumference was associated with greater all‐cause mortality (HR, 1.17; 95% CI, 1.06‐1.30) and cancer‐specific mortality (HR, 1.22; 95% CI, 1.04‐1.42). Conclusions: Among postmenopausal women diagnosed with cancer in the WHI, cardiometabolic risk factors before the cancer diagnosis were associated with greater all‐cause, CVD, cancer‐specific, and other‐cause mortality. These results raise hypotheses regarding potential clinical intervention strategies targeting cardiometabolic abnormalities that require future prospective studies for confirmation. Lay Summary: This study uses information from the Women's Health Initiative (WHI) to find out whether cardiac risk factors are related to a greater risk of dying among older women with cancer. The WHI is the largest study of medical problems faced by older women in this country. The results show that women who have 3 or 4 risk factors are more likely to die of any cause, heart disease, or cancer in comparison with women with no risk factors. It is concluded that interventions to help to lower the burden of cardiac risk factors can have an important impact on survivorship among women with cancer. Abstract : Among postmenopausal women with select early‐stage cancers associated with metabolic syndrome, a higher number of cardiometabolic abnormalities is associated with a significantly higher risk of overall death in addition to a higher risk of death due to cancer, heart disease, and other causes. These findings highlight a major gap in the care of patients with cancer and the need for improved efforts by public health systems to improve cancer survivorship.